Laparoscopic operation of hepatic hydatid cyst with intraabdominal dissemination : a case report and literature review - Bušić, Željko, liječnik, 1953.- (Array, 2009)
Summary: Hepatic hydatid cysts are a serious medical problem in some regions like Mediterranean region. In Croatia 25–30 new cases of hepatic hydatid cysts are recorded each year. In University Hospital Dubrava 7 patients with hepatic hydatid cysts were operated in 2008. Surgical approach recognizes open laparotomy and laparoscopy. The case and technique of laparoscopic operation of hepatic hydatid cyst in seventh segment and three disseminated intraabdominal cysts is described. Laparoscopy should be attempted even in complex cases with dissemination